2013
DOI: 10.1007/978-3-642-39176-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Towards Modeling and Model Checking Fault-Tolerant Distributed Algorithms

Abstract: Abstract. Fault-tolerant distributed algorithms are central for building reliable, spatially distributed systems. In order to ensure that these algorithms actually make systems more reliable, we must ensure that these algorithms are actually correct. Unfortunately, model checking state-ofthe-art fault-tolerant distributed algorithms (such as Paxos) is currently out of reach except for very small systems. In order to be eventually able to automatically verify such fault-tolerant distributed algorithms also in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…All of our benchmark algorithms were originally published in pseudocode, and we model them in a parametric extension of Promela, which was discussed in [27,34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of our benchmark algorithms were originally published in pseudocode, and we model them in a parametric extension of Promela, which was discussed in [27,34].…”
Section: Methodsmentioning
confidence: 99%
“…Waiting for majorities, or more generally waiting for quorums, is a key pattern of many faulttolerant algorithms, e.g., consensus, replicated state machine, and atomic commit. In [34] we introduced an efficient encoding of these algorithms, which we used in [33] for abstractionbased parameterized model checking of safety and liveness of several case study algorithms, which are parameterized in the number of processes n and the fraction of faults t, e.g., n > 3t. In [41] we were able to verify reachability properties of more involved algorithms by applying bounded model checking.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, for a long time, it has been observed that counter systems [14,15,17] can be sufficient to specify many problems (like cache coherence or broadcast protocols) in the distributed algorithms area. Recently, counter abstractions have been effectively used also in the verification of fault-tolerant distributed protocols [3,[25][26][27]. It should be noticed that, unlike what happens in the old framework of [14,15,17], these new applications are often (although not always) based on abstractions that can only simulate the original algorithms and such simulation may sometimes be the result of an a priori reasoning on the characteristics of the algorithm, embedded into the model.…”
Section: Introductionmentioning
confidence: 99%
“…The latter makes it imperative to handle multiple parameters such as n, t, and the number f of faulty processes in a run of the algorithm, as well as resilience conditions such as n > 3t ∧ f ≤ t. In the context of fault-tolerant distributed algorithms, model checking was hence limited to verifying small system instances. For instance, the authors of [18,17,11,9] fixed the number n of processes a priori to some small value, say, n = 4 to 10, and used model checking for ruling out errors in these particular system instances. Although it is tempting to verify a "large enough" model and assume that this implies the algorithm's correctness in the general case, this is not necessarily true.…”
mentioning
confidence: 99%
“…However, for our abstraction method, a new variant of control flow automata (CFA) [5] is more natural, and the ways to express nondeterminism in our CFA variant are particularly suitable to model the influence of faults and uncertain message delays. In [8], we describe in detail how fault-tolerant message passing algorithms are specified using CFAs. As the CFA formalism is rather low-level compared to the way distributed algorithms are typically stated in the literature, interfaces to higher-level languages are subject to future work.…”
mentioning
confidence: 99%